2017
DOI: 10.24323/akademik-gida.370103
|View full text |Cite
|
Sign up to set email alerts
|

Karbon Fiber Destekli Kabin Kurutucuda Farklı Sıcaklıklarda Elma Dilimlerinin Kurutulmasının İncelenmesi: Kurutma Karakteristikleri ve Performans Değerlendirmesi

Abstract: Investigation of Drying of Apple Slices in Carbon Fiber Assisted Cabin Dryer at DifferentTemperatures: Drying Characteristics and Performance Evaluation ABSTRACT Drying behaviour of apple slices in carbon fiber assisted cabin dryer (CFACD) was investigated, and performance evaluation of the process was conducted. The compatibilities of fourteen different thin layer drying models to the experimental data were examined. The highest corrected coefficient of determination, the lowest reduced chi-square and the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
(49 reference statements)
0
8
1
1
Order By: Relevance
“…Cokgezme et al (2016) reported that exergy efficiency of thin layer strawberry samples (55, 60, and 65°C at a rate of 0.8 ± 0.05 m/s) with CFACD process was in the range of 24.62% and 29.83%, and it increased as the drying temperature increased. Similarly, the exergy efficiency of apple slices dried at three different drying temperatures (60, 70, and 80°C) by CFACD process was in the range of 9.44% and 11.64%(Pekdoğan Göztok & Icier, 2017). It was thought that the energy and exergy values reported by the researchers for ID and CFACD methods were lower than values predicted in present study because of the different drying temperatures and the food material used.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Cokgezme et al (2016) reported that exergy efficiency of thin layer strawberry samples (55, 60, and 65°C at a rate of 0.8 ± 0.05 m/s) with CFACD process was in the range of 24.62% and 29.83%, and it increased as the drying temperature increased. Similarly, the exergy efficiency of apple slices dried at three different drying temperatures (60, 70, and 80°C) by CFACD process was in the range of 9.44% and 11.64%(Pekdoğan Göztok & Icier, 2017). It was thought that the energy and exergy values reported by the researchers for ID and CFACD methods were lower than values predicted in present study because of the different drying temperatures and the food material used.…”
contrasting
confidence: 54%
“…This can be explained by the fact that drying temperature and final moisture content reached were lower than in this study. In another recent study (Pekdoğan Göztok & Icier, 2017), apple slices with an initial moisture content of 86 ± 2% were dried to 10 ± 0.6% moisture content using CFACD process at three different drying temperatures (60, 70 and 80°C).…”
Section: Effects On Drying Characteristics and Temperature Distribumentioning
confidence: 99%
See 1 more Smart Citation
“…Hot air drying is a process based on removing moisture from food under a continuous flow of hot air. This drying method is more preferred especially due to its low cost (Göztok, 2017). However, microwave drying has advantages such as short processing time, high product quality and low energy consumption compared with hot air drying.…”
Section: Introductionmentioning
confidence: 99%
“…Sun drying is a preferred method because it is economical and does not require investment, but it is a disadvantageous method due to microbial reliability and loss in quality such as color and aroma (Göztok and Içier, 2017).…”
Section: Drying Characteristics Of Goji Berry Fruitmentioning
confidence: 99%